Characterization and modelling of thermal protective performance of fabrics under different levels of radiant-heat exposures. (February 2019) - Mandal, Sumit; Annaheim, Simon; Camenzind, Martin; Rossi, René M
The investigation of thermal protective performance of fabrics is highly relevant in order to procure and further develop the firefighters' protective clothing. Therefore, this paper aims at investigating the thermal protective performance of fabrics used in firefighters' clothing under different levels of radiant-heat exposures. For this, properties of a set of thermal protective single- and multi-layered fabrics were measured, and these fabrics were tested under radiant-heat exposures using the Method B of ISO 6942:2002 standard. During the testing, fabrics were exposed to low (10 kW/m 2 ), medium (40 kW/m 2 ), and high (80 kW/m 2 ) intensity radiant-heat exposures; and the heat transfer level (i.e., time required to increase the skin temperature of a wearer/firefighter by certain degrees) through these fabrics were calculated to measure their thermal protective performance. The effects of fabric parameters, structures, properties, and radiant-heat intensities on the protective performance were characterized, and fabric properties that significantly affected the protective performance were statistically identified at different level of radiant-heat exposures. It has been found that weight, thickness, thermal resistance, and evaporative resistance can positively affect the protective performance. Also, the significant fabric properties affecting the protective performance vary for single- and multi-layered fabrics. By using these significant properties, the protective performance of single- and multi-layered fabrics were also separately predicted by mathematical models, i.e., multiple linear regression models and multiple logarithmic regression models. As per the findings of this study, multiple linear regression models can effectively be used to predict the thermal protective performance of fabrics. This study will lead towards building a better understanding and prediction of thermal protective performance of fabrics under radiant-heat exposures.